Glyburide Transport Across the Human Placenta. Issue 3 (March 2015) - Schwartz, Rachelle A.; Rosenn, Barak; Aleksa, Katarina; Koren, Gideon
Abstract : OBJECTIVE: To estimate the magnitude of transplacental transfer of glyburide in women with gestational diabetes mellitus (GDM). METHODS: A prospective, observational study was conducted on women with GDM on glyburide therapy. On delivery admission, the glyburide dose and time of last dose were recorded. Immediately postdelivery, maternal and umbilical venous blood samples were obtained and the concentrations of glyburide were determined by high-performance liquid chromatography–mass spectrometry with a limit of detection of 0.25 ng/mL. RESULTS: Nineteen patient dyads were analyzed. The mean total daily maternal glyburide dose was 6.6±6.3 mg per day and the mean time between last dose and sampling was 13.3±6.5 hours. The mean maternal serum glyburide level at birth was 15.4±20.8 ng/mL, whereas the mean umbilical glyburide level was 7.5±8.2 ng/mL, which showed a statistical correlation ( r 2 =0.72, P <.01). There were statistically significant relationships between total maternal glyburide dose (1.25–20 mg per day) and maternal glyburide levels (0.93–70.71 ng/mL; r 2 =0.46, P ⩽.01) and between total maternal glyburide dose and umbilical glyburide levels (0.95–32.41 ng/mL; r 2 =0.43, P ⩽.01) However, we observed wide variability in maternal and umbilical glyburide levels at both extremes of the total glyburide dose. Seventy-nine percent of cord samples (15/19) had glyburide levels less than 10 ng/mL (the limit of detection reported in earlier studies) and 37% (7/19) were higher than the corresponding maternal samples. CONCLUSION: Transplacental transfer of glyburide is highly variable among patients, corroborating ex vivo placental perfusion studies showing a transport-mediated glyburide efflux from the fetal to the maternal circulation. In most neonates (79%), glyburide levels were below 10 ng/mL. LEVEL OF EVIDENCE: III Abstract : In vivo transplacental transfer of glyburide does occur and results in low fetal concentrations.